1996
DOI: 10.1021/la960198u
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Formation of ZrO2 in the Reaction of ZrCl4 Vapor with Porous Silica and γ-Alumina Surfaces

Abstract: The reaction of ZrCl4 vapor at 300, 450, and 600 °C with silica and γ-alumina preheated at 300 and 600 °C was studied by XRD, FTIR, 1H MAS NMR, and chemical etching with sulfuric acid. NMR and FTIR revealed a consumption of OH groups in the reaction. However, subsequent water vapor treatment brought some of the OH groups of the support back, indicating that part of the surface had been directly chlorinated. The ratio between permanently consumed OH groups and directly chlorinated OH groups depended on the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 42 publications
5
68
0
Order By: Relevance
“…[7,8] The ZrO 2 formation in the ZrCl 4 chemisorption on high surface area substrates has a similar temperature dependency. [9] d #2. The TiO 2 particles formed in the TiCl 4 reaction with high surface area silica are crystalline and have either anatase or rutile structure, [8,33] which phase is formed depending on both reaction temperature and on substrate heat-treatment temperature.…”
Section: Secondary Reactions Of Hclmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,8] The ZrO 2 formation in the ZrCl 4 chemisorption on high surface area substrates has a similar temperature dependency. [9] d #2. The TiO 2 particles formed in the TiCl 4 reaction with high surface area silica are crystalline and have either anatase or rutile structure, [8,33] which phase is formed depending on both reaction temperature and on substrate heat-treatment temperature.…”
Section: Secondary Reactions Of Hclmentioning
confidence: 99%
“…[15,16] In 1996, Kytökivi et al [9] reported the existence of ZrO 2 particles when they investigated the ZrCl 4 chemisorption on porous high surface area silica and alumina. Compared to the TiO 2 particles observed on high surface area substrates, the ZrO 2 particles were considerably smaller, with dimensions in the order of 10 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a number of examples showing that under CVD conditions, usually below 1000 C, cubic zirconia may form. [26,30,31,45] This is often attributed to growth kinetic and nucleation influences.…”
Section: Crystallinity and Phase Distributionmentioning
confidence: 99%
“…Examples include oxygen-conductive membranes for use in fuel cells and oxygen sensors, [1±8] high-temperature thermal barrier coatings, [9±12] hard protective layers, [13±15] ferroelectric films, [16±22] optical coatings, [23±25] catalysts, [26,27] and buffer layers for superconductor growth. [28,29] For most applications, the yttriumstabilized tetragonal and cubic (ªYSZº) zirconia modifications are used, due to their superior toughness.…”
Section: Introductionmentioning
confidence: 99%